Screening accuracy of PAP and VIA in terms of Colposcopy guided cervical biopsy: A comparative study - Mitra, Partha Sarathi; Na, Abhoy Chand; Barman, Medhatithi; Roy, Debobroto; Shankar, Tara; Naskar, Tapan Kumar (Journal of Midwifery, 2023)
Introduction: Approximately 80% of cervical cancer occurs in developing countries of which India contributes about 20-30% of the global burden. WHO considers cervical cancer as a preventable disease because it can be diagnosed in its precancerous phase. Cytology and VIA for screening and colposcopy for directed biopsy jointly may achieve accuracy of approximately 90% to 99%.Methods: An observational cross sectional comparative study was performed to find accuracy of screening protocols of exfoliative cervical cell cytology and visual inspection under acetic acid in terms of the diagnostic test of Colposcopy guided biopsy on 300 symptomatic women of age 18-60 years over the period of one year.Result: Both PAP and VIA positivity increased with age, increasing parity, gynaecological symptoms. PAP and VIA positive results co related with Colposcopy directed biopsy histopatholgy reports in a statistically significant proportion.Discussion: VIA can screen out a large number of women suspected to have cervical cancer in an easy method done in OPD in naked eye and does not require any meticulous microscopic examination with a high degree of sensitivity and high false positivity but on the other hand PAP was less sensitive but more specific test when both combined with Colposcopy guided biopsy.Conclusion: The associations between distribution of women who were Pap +ve and histology +ve as well as VIA and histo +ve were statistically significant.